Open vs Percutaneous Pedicle Screw Fixation in Thoraco-Lumbar Traumatic Fracture - Muhammad Faisal Karim, Sana Ullah, Muhammad Muneeb Zaman, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Thoracolumbar fractures are commonly managed using open transpedicular fixation; however, minimally invasive techniques such as percutaneous pedicle screw fixation have been increasingly adopted due to their potential advantages. Emerging evidence suggests improved perioperative outcomes with the percutaneous approach compared to the conventional open method. Objective: To compare the outcomes of open versus percutaneous pedicle screw fixation in patients with thoracolumbar traumatic fractures. Materials and Methods: This randomized controlled trial was conducted at the Department of Neurosurgery, Mayo Hospital, Lahore, from March 2021 to September 2021. A total of 60 patients meeting the inclusion and exclusion criteria were enrolled and randomly allocated into two equal groups using the lottery method. Group A underwent percutaneous pedicle screw fixation, while Group B underwent open pedicle screw fixation. All procedures were performed under general anesthesia by a single surgical team. Intraoperative parameters including operative time, incision length, and blood loss were recorded, while postoperative hospital stay was also documented for comparison. Results: The mean age of patients in Group A and Group B was 35.80±8.74 years and 40.76±14.30 years, respectively, with male predominance in both groups. Group A demonstrated significantly better outcomes compared to Group B in terms of operative time (44 vs. 74.03 minutes, p<0.001), incision size (26.70 vs. 67.86 mm, p<0.001), intraoperative blood loss (51.33 vs. 215.33 mL, p<0.001), and hospital stay (1.00 vs. 2.60 days, p<0.001). Conclusion: Percutaneous pedicle screw fixation is superior to open pedicle screw fixation for the management of thoracolumbar traumatic fractures, offering significant advantages in operative time, surgical invasiveness, blood loss, and duration of hospitalization. Keywords: Outcome, Open, Percutaneous, Pedicle, Screw Fixation, Thoracolumbar, Traumatic, Fracture.